An unusual presentation of partial hemifacial hyperplasia - Date, Amit S.; Pawar, Amrapali Keny; Kamath, Pooja; Pereira, Treville (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Partial hemifacial hyperplasia is a rare congenital malformation characterized by prominent unilateral overdevelopment of some of the hard and soft tissues of the face. This uncommon diagnosis should be considered while examining facial asymmetry. We report a case of slowly enlarging right facial swelling which turned out to be enlarged zygomtic arch. Complete evaluation led us to believe continued condylar hyperactivity as the underlying reason for worsening deformity. We offer an explanation for the same. Minimal surgical intervention led to significant aesthetic improvement which was patients main concern.